Assessment of glibenclamide pharmacokinetics in poloxamer 407-induced hyperlipidemic rats - Yousef A. Bin Jardan (Saudi Pharmaceutical Journal, 2021)
The aim of the present research was to describe the consequences of hyperlipidemia (HL) on the pharmacokinetics of glibenclamide (Gb) in poloxamer 407-induced hyperlipidemic rats. Rats were given intraperitoneal dose of poloxamer 407 to cause hyperlipidemia. A single oral dose of Gb (10 mg/Kg) was given to normal and HL rats. The Cmax and tmax after oral dose of Gb in normal rats were 340.10 µg/ml and 3.67 h, respectively. Whereas, the Cmax and tmax after oral dose of Gb in HL rats were noted as 773.39 µg/ml and 2.50 h respectively. The AUC value of Gb was found considerably higher in the HL rats. While the plasma clearance (CL) after oral dose of Gb was 2.53 ml/h and 1.39 ml/h in normal and HL rats respectively. The improved plasma concentration of Gb following oral dosing in rats with HL seems to be due to a direct influence on hepatic clearance or metabolizing enzymes. In conclusion, the Gb pharmacokinetics was considerably affected by the HL in rats. Such findings play an important role for predicting the alterations in the pharmacokinetics of drugs including GB, in cases having hyperlipidemia.